Golput Dalam Tinjauan Hadis - Siregar, Muhammad Nuh; Harahap, Alwi Padly; Siregar, Rois Hamid (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
The phenomenon of abstention can be identified with voting behavior, because voting behavior itself in political science is defined as the participation of citizens in general elections whether they choose to exercise their right to vote or not. This research aims to find out abstentions in hadith reviews. The application of qualitative methods is used to critically analyze the arguments surrounding hadith which are closely related to the abstention phenomenon. The results of this research show that leadership in Islam is very important. This can be seen from the many verses of the Koran and hadith that explain leadership. That power is the ruler who makes Islamic law the highest law that governs the country. The existence of Islamic law would not be important if it only existed in the writings of Islamic legal experts. Thus Islamic law requires a ruler who implements it. The appointment of a ruler who is committed to the implementation of Islamic law is chosen by democratic voting. A person's right to vote will be very important in determining leadership. For this reason, abstention is not permitted in Islamic law.